Langt ude på landet i Latinamerika - Schioler, Ebbe (Udenrigsministeriet, Danida, 2001)
Latin America has given the world many of its key agricultural products. Food crops like potatoes, sweet potatoes, maize, beans, and many, many others have traveled far and wide....[It] is one of the richest concentrations of biodiversity on the face of the globe.....Today, however, many people in rural Latin America live in extreme poverty....At the same time, the rich mountain and lowland ecosystems of the American tropics are threatened by degradation and loss of species.....Ebbe Schiøler -- an intrepid traveler and untiring observer of the CGIAR and of the work of the Future Harvest centers it supports -- has journeyed to seven countries to gather, first-hand, the stories of the men and women who benefit on a day-to-day basis from the research of the centers." (From Foreword by Hubert Zandstra, Chairman of the Board, Future Harvest)